Strategic Alliance in the Creative Economy:Acquisition Coach's of Kate Spade - Daryanto Hesti Wibowo (Majalah Ilmiah Bijak, 2021)
This study is an analytical research on the application of strategic alliances in the creative economy in a global context. Creative economy is not just about small and medium scale industry, but its economic potential is very gigantic. The world trade in creative industry-based goods and services in the Special Edition of the United Nations Creative Economy Report, has recorded a trade of USD 624 billion in 2011. This study analyzes the acquisition of Coach's exclusive handbag company against its competitor, Kate Spade. Using the literature and business information, the analysis shows that the acquisition of May 2017 is a Coach reaction to the tight competition dynamics in the exclusive handbag industry. In order to win the competition, Coach decided to acquire Kate Spade worth USD 2.4 billion or around IDR 31.9 trillion. With this acquisition value, Coach hopes to boost its sales performance through market expansion by leveraging the competitive advantage of its partner Kate Spade.  This analysis can be used as a reference for the creative economy development in Indonesia, especially handbag industry which is currently starting to penetrate international markets such as Dowa and Laga.